The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1093/cvr/cvz314
|View full text |Cite
|
Sign up to set email alerts
|

Aging influences cerebrovascular myogenic reactivity and BK channel function in a sex-specific manner

Abstract: Aims The myogenic reactivity of the middle cerebral arteries (MCA) protects the brain by altering the diameter in response to changes in lumen pressure. Large conductance potassium (BK) channels are known to regulate the myogenic reactivity, yet, it is not clear how aging alters the myogenic reactivity via the BK channel in males and females. Thus, we hypothesize that age-associated changes in BK channel subunits modulate the myogenic reactivity in a sex-specific manner. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…Calcium-activated K + channels are a negative feedback mechanism resulting in VSMCs membrane hyperpolarization and reduced vasoconstriction ( 8 , 53 ). A recent study indicated that VSMCs isolated from MCAs of adult female rats exhibited higher BK channel current densities compared with males leading to attenuated myogenic reactivity ( 61 ). In addition, a higher basal vascular tone would be expected to blunt subsequent myogenic responses ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium-activated K + channels are a negative feedback mechanism resulting in VSMCs membrane hyperpolarization and reduced vasoconstriction ( 8 , 53 ). A recent study indicated that VSMCs isolated from MCAs of adult female rats exhibited higher BK channel current densities compared with males leading to attenuated myogenic reactivity ( 61 ). In addition, a higher basal vascular tone would be expected to blunt subsequent myogenic responses ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Stroke survivors face long-term disability and cognitive deficits ( 37 ). Previous studies demonstrated that females have smaller MCA compared with males in humans ( 45 , 51 , 64 ) and in rats ( 61 ). The MCA in females has greater responses to hypercapnia, nitric oxide (NO), and flow-mediated vasodilation ( 31 , 47 , 54 , 56 ) and lower responses to angiotensin II (ANG II) as well as endothelin-1 (ET-1)-induced vasoconstriction ( 1 , 62 ).…”
Section: Introductionmentioning
confidence: 95%
“…However, it was also reported that NS1619 can also cause vasodilation by affecting multiple complementary pathways, including the stimulation of NO production, regulating other K + channels and L-type Ca 2+ channels (McCullough et al, 2014), i.e., NS1619 may have a nonspecific activation effect on BK channel activation. Besides that, more and more studies have reported that NS1619 is the activator of the BK-α subunit (Reed et al, 2019;Du et al, 2020). Therefore, the single experiment of vascular response to NS1619 is not enough to prove the effect of the BK channel.…”
Section: Regulation and Mechanisms Of Coronary Bk-β1 By Murf1mentioning
confidence: 99%
“…Finally, aside from estrogenic endothelial/myogenic and anti-inflammatory effects, there have been documented differences in potassium channel expression in males vs. females, with a direct link to estrogen levels ( Reed et al, 2020 ). In rats, large potassium channel beta-1 subunit (BK-B1) displays decreased expression in both males and female rats with removed ovaries.…”
Section: Considerations and Future Directionsmentioning
confidence: 99%